Partisipasi Pelajar Kalimantan di Ilmupedia Berani Jawab: Gamifikasi, Literasi Digital, dan Ekosistem Bisnis Telkomsel - Salsabila, Luizya; Zaini, Muhammad (YASIN, 2025)
Although gamification has been extensively studied in digital education, research that specifically examines digital education competitions as a strategy for simultaneously enhancing literacy and strengthening business ecosystems remains limited, particularly in Kalimantan. This study aims to analyze the participation of students in Kalimantan in Ilmupedia Berani Jawab (IBJ) Season 5 and 6 and to evaluate the effectiveness of gamification in increasing learning engagement. A descriptive quantitative approach was employed by processing the entire population in the official IBJ database, comprising 2,585 participants (878 teams) in Season 5 and 8,297 participants (2,933 teams) in Season 6. The data were tabulated and analyzed to identify patterns of participant distribution across districts and provinces in Kalimantan. The findings show a more than threefold increase in participation, accompanied by a shift in the participation center from Tarakan in Season 5 to Samarinda in Season 6. Gamification elements such as points, leaderboards, and time limits were found to increase participants’ motivation, focus, and consistency in completing challenges. In addition to educational benefits, IBJ also contributes to user engagement and the strengthening of Telkomsel’s digital ecosystem in the student segment. This study enriches the literature on gamification and digital participation beyond Java and offers recommendations for organizers to improve equitable access, strengthen infrastructural support, and develop evaluation features. Future studies are recommended to combine quantitative and qualitative methods to explore participants’ experiences in greater depth.